Identification of Colletotrichum brevisporum causing anthracnose on passion fruit. Issue 4 (2nd October 2017) - Du, Yi-Xin; Shi, Niu-Niu; Chen, Wen-Le; Ruan, Hong-Chun; Yang, Xiu-Juan; Gan, Lin; Dai, Yu-Li; Chen, Fu-Ru
Abstract: Passion fruit ( Passiflora edulis Sims.) has become an important commercial fruit with large-scale cultivation in China. A disease affecting the stems, fruits, leaves and tendrils was observed on passion fruit vines in Sanming, Fujian Province, China, in August 2015. The typical symptoms included lesions of oval to irregular shapes, brown to brownish black in colour, with sunken cavities. Acervuli and dark setae were observed within the lesions. The disease incidence varied from 25 to 60% in different fields. The causative pathogen was identified as Colletotrichum brevisporum on the basis of morphological characteristics and sequence analysis of the internal transcribed spacer (ITS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), beta-tubulin 2 (Tub2) and actin (ACT) genes. Pathogenicity was confirmed by fulfilling Koch's postulates on plants and detached fruit. To our knowledge, this is the first report of anthracnose disease on passion fruit caused by C. brevisporum worldwide.